Novel Benchtop Magnetic Particle Spectrometer for Process Monitoring of Magnetic Nanoparticle Synthesis - Löwa, Norbert (Nanomaterials (Basel), 2020)
Magnetic nanoparticles combine unique magnetic properties that can be used in a variety of biomedical applications for therapy and diagnostics. These applications place high demands on the magnetic properties of nanoparticles. Thus, research, development, and quality assurance of magnetic nanoparticles requires powerful analytical methods that are capable of detecting relevant structural and, above all, magnetic parameters. By directly coupling nanoparticle synthesis with magnetic detectors, relevant nanoparticle properties can be obtained and evaluated, and adjustments can be made to the manufacturing process in real time. This work presents a sensitive and fast magnetic detector for online characterization of magnetic nanoparticles during their continuous micromixer synthesis. The detector is based on the measurement of the nonlinear dynamic magnetic response of magnetic nanoparticles exposed to an oscillating excitation at a frequency of 25 kHz, a technique also known as magnetic particle spectroscopy. Our results underline the excellent suitability of the developed magnetic online detection for coupling with magnetic nanoparticle synthesis based on the micromixer approach. The proven practicability and reliability of the detector for process monitoring forms the basis for further application fields, e.g., as a monitoring tool for chromatographic separation processes.